The marketability of diet consult as a tool for diet recommendation (Journal of the Nutritionist-Dieticians' Association of the Philippines, 2011)
Diet Consult is a nutrition software, available either in a compact disk or through a vending machine, which can recommend diets to individuals appropriate for their age, sex, height, weight, and health condition. A consumer research focusing on the marketability of Diet Consult was contracted outside the Food and Nutrition Research Institute (FNRI) to avoid bias results. The main objective was to determine the marketability of Diet Consult to potential users in terms of gender, age group, socio-economic class, and the amount customers are willing to pay for the software or use of the vending machine. The questions on marketability were incorporated in the Omnibus study of AC Nielsen. The study interviewed 800 respondents selected through a stratified sampling of 12-60 years old individuals from both sexes in 800 households from AB, C, D, and E socio-economic classes in Metro Manila. The intent to use the nutrition software was expressed by 38% of respondents, who were largely female, aged 18-45 years old or 56-60 years old, who were from the upper to middle socio-economic class, and were willing to pay PhP 100 for the software. On the other hand, 41% who were interested to use the vending machine were mostly female of middle age (26-35 years old), from upper to middle socio-economic class, and were willing to pay P24. It is recommended that a cost-benefit analysis be undertaken since a potential market exists for utilization of Diet Consult.